Reporting and Recording Post-2012 GHG Mitigation Commitments, Actions and Support - Ellis, Jane (OECD Publishing, 2009)
The Bali Action Plan (BAP) indicated the importance of "measurable, reportable and verifiable" (MRV) greenhouse gas (GHG) mitigation actions and commitments, as well as support for GHG mitigation actions, in the post-2012 climate framework. Negotiations underway for this framework have highlighted the benefits of, and interest in, expanding current MRV-related provisions, including to develop a more comprehensive and timely picture of countries' mitigation efforts and support. Establishing some form of reporting or recording mechanism that could be used to centralise and track information on country mitigation actions, commitments and support could fill this gap. This mechanism could focus on current efforts, or also include information on future or planned efforts. Such a mechanism could take different forms, including a stand-alone electronic registry where actions (and potentially also commitments and support) could be reported ex post. Alternatively, information on actions and commitments could be recorded ex ante as an integral appendix of a post-2012 climate agreement. This paper explores the possible purposes, coverage and form of such a reporting/recording mechanism (subsequently referred to as a NAMAs registry); what information it could include in terms of actions, commitments and support; and the institutional implications of different design options. It thus focuses on the measurable and reportable components of MRV, rather than on verification
Keywords: Energy; Environment